THE TRANSLATION OF INDONESIA MYTH CHARACTERS ON THE ENGLISH WIKIPEDIA - Marisa Puteri Sekar Ayu Santosa (Asosiasi dosen IDEBAHASA KEPRI, 2020)
The English language Wikipedia is in both terms of the number of articles and amount of content, the largest encyclopedia ever written. Since it has an enormous amount of information and ease of access through the internet, Wikipedia is often used as the first destination for the general public when they wish to find specific information or learn about particular topic. One of the biggest issues in Wikipedia is making information available in almost all languages. English Wikipedia is often using another language as the source language for translation activities aimed to enhance the quality of the multilingual Wikipedia, one of the examples is Indonesian. In this research, the researcher was interested in observing Indonesian myth characters on the English Wikipedia by investigating the kind of translation techniques that English-Wikipedia used and the way of Wikipedia translated the cultural terms. This research used comparative descriptive method which compares the source text (Indonesia Wikipedia) and the target text (English Wikipedia). The Indonesian myths characters that the researcher wanted to analyze were: Sundel Bolong, Pocong, Jenglot, Wewe Gombel, Kuntilanak, Tuyul, Nyai Roro Kidul, and Babi Ngepet by using translation techniques from Molina and Albir (2002. The result of the study, it could be shown that there were 9 types of translation techniques which are used, they were: amplification (addition), borrowing, compensation, discursive creation, established equivalence, literal translation, modulation, reduction (omission), and transposition. Moreover, the translated text was more informative than the source text, since it was impossible to literally translating the cultural terms.